AWARENESS ON GST (GOODS AND SERVICE TAX) AMONG GENERAL PUBLIC IN THIRUVANANTHAPURAM DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
Goods and Service Tax is something that the general public is dealing with on their daily lives. Therefore, their awareness and satisfaction are analysed in this work. The data were collected from both primary and secondary source and the respondents were selected using convenient sampling among respondents in Thiruvananthapuram District. The study explains that there is difference in the awareness on the basis of gender and educational qualification and no difference on the basis of age. It also reveals that level of satisfaction on Price of products after GST has association with age.